Condensation of Indole with Isatin over AlCl3/Mesoporous Aluminosilicate - Tri Esti Purbaningtias; Didik Prasetyoko; Hasliza Bahruji; Yusuf Muhammad Zein; Sugeng Triwahyono; Arief Fadlan; Imroatul Qoniah (Indonesian Journal of Chemistry, 2015)
Aluminium chloride immobilized on mesoporous aluminosilicate was investigated as catalysts in the condensation of isatin with indole. AlCl3/mesoporous aluminosilicate (AlCl3/AM) catalysts were prepared by impregnation of 1, 5, 10 and 15 wt% AlCl3 on the surface of mesoporous aluminosilicate. A maximum conversion of isatin was achieved using 15% AlCl3/AM catalyst whereas the highest selectivity of 68.97% towards trisindoline was obtained using pure AM. The activity of the catalysts was depended on their acid site number and surface area. The number of Brønsted acid and the surface area affected to the conversion of isatin while the total acidity and the number of Lewis acid influenced the selectivity.